Mission Accomplished ? : The Crisis of International Intervention - Jenkins, Simon (London I.B. Tauris & Co. Ltd., 2015)
From Vietnam to Syria, politicians, commentators and journalists have argued for and against intervention, whether it is military or humanitarian. Simon Jenkins here presents his extensive writings, charting the history of and the arguments surrounding intervention in Kosovo, Afghanistan, Iraq, Libya and Syria. Do nations intervene because of right and wrong? Is it simply a form of 'imperialism-lite'? When is intervention justified? He traces the evolution of "liberal interventionism" and shows that scepticism towards it came and comes not just from a growing perception of its failure. Instead, he argues, that it displays worrying signs of merely laundering old-fashioned western imperialism, bordering at times on a crusader complex. The language and declared motives might be novel, but victim nations could be forgiven for wondering otherwise. Jenkins here provides a much-needed and timely look at key instances - and mistakes - of international intervention in recent history.
Include Index and Epilogue
Keywords: Intervention (International law) -- Intervention (International law)--Moral and ethical aspects